Stem Cell Therapy for Myocardial Infarction Recovery: Advances, Challenges, and Future Directions - Nicholas T. Le; Matthew W. Dunleavy; William Zhou; Sumrithbir S. Bhatia; Rebecca D. Kumar; Suyin T. Woo; Gonzalo Ramirez-Pulido; Kaushik S. Ramakrishnan; Ahmed H. El-Hashash (Biomedicines)
Myocardial infarction (MI) is a leading cause of morbidity worldwide, resulting from ischemic damage and necrosis to cardiomyocytes. While the standard treatment regimen for MI can be successful in restoring coronary perfusion, it typically does not resolve myocardial damage, which can leave patients particularly vulnerable to complications such as heart failure or electrical conduction abnormalities. Stem cell therapies offer a promising novel approach aimed at restoring cardiac function and decreasing the incidence of functional complications after an MI. This review used a literature search to evaluate the current landscape of stem cell therapy for post-MI recovery and focuses on the stem cell candidates for MI recovery therapy, delivery methods of such treatment, and their effectiveness. Both preclinical and clinical trials have demonstrated the safety of stem cells, but have struggled with limited cell retention, inconsistent efficacy, and survival. Mechanisms are employed by stem cells to promote regeneration, such as paracrine signaling, angiogenesis, and structural remodeling, in addition to the various stem cell delivery methods, including intracoronary infusion, direct myocardial injection, and intravenous administration. Furthermore, some strategies to combat past challenges in this field are discussed; for instance, extracellular vesicles, bioengineered patches, hydrogels, gene editing, and bioprinting. This article will provide a framework for future research in stem cell therapies and highlight the current progress in the field.